Evaluation of the practicality of project-based learning implementation plan in light vehicle engine maintenance using ADDIE approach - Muslim, Muslim; Kuo, Hsu-Chan; Setiawan, Dedi; Fernandez, Donny; Putra, Rido; Derisman, Aken; Zikri, Zikri (Jurnal Inovasi Teknologi Pendidikan, 2024)
Light vehicle engine maintenance is an important subject in automotive vocational education. However, several problems need to be overcome, such as the lack of student involvement in learning, which creates a gap between theoretical and practical learning. To overcome this problem, a project-based learning implementation plan (LIP) was developed which has been proposed as an approach capable of integrating theory and practice, as well as increasing student involvement in learning. This research aims to evaluate the practicality of product development in the form of a project-based LIP on light vehicle engine maintenance. This study uses an R&D approach as well as the ADDIE model procedure. The subjects in this study were 5 experts who came from productive teachers. The instruments used are interview sheets for observation activities and instruments in the form of response questionnaires to obtain product practicality data. The analysis technique at the practicality criteria level uses a practicality value formula in percentage form. The research results have found that the practicality of the product implementation plan for project-based learning in light vehicle engine maintenance learning is based on teacher responses which have been analyzed so that it is stated in the convenient category. This study concludes that the project-based lesson plan developed has high practicality in learning light vehicle engine maintenance. Further research can test the effectiveness of project-based learning implementation plans on a larger scale by involving more students and educational institutions and integrating modern technologies such as augmented reality or virtual reality into the learning implementation plans.